A study on the effect of coaching feedback on the motivation of street dancers - Gasacao, Katrina R. 2000-; Brebante, Zyra Ruth T. (College of Human Kinetics, University of the Philippines Diliman Quezon City, 2023)
Coaches' feedback significantly impacts the performance and motivation of players, and a lack of drive and enjoyment can contribute to youth athletes quitting their sport. This study aims to determine the effects of coaching feedback on the motivation of street dancers. The participants in this study were 22 street dancers, 11 male, and 11 female, from a street dance team in Metro Manila. An interview questionnaire was distributed to the participants to understand better the effects of coaching feedback on the motivation of street dancers. Afterward, focus group discussions were conducted to dig deeper and collect more information. The participants were grouped into three groups according to their preferred feedback - positive, negative, and both positive and negative verbal feedback. All the information was analyzed through content analysis, specifically relational analysis, wherein the researcher will identify specific words, topics, or concepts in a given set of qualitative data. This study found that both positive and negative verbal feedback impacted the motivation of street dancers. Different types of feedback had varying effects on the motivation of street dancers, and no type of feedback was consistently more effective. Most participants preferred negative feedback as it motivated them to correct errors quickly, while positive feedback motivated them to perform well and feel happy. Both types of feedback also motivated participants to achieve their goals and impress their coach. Standardized feedback may not be effective for all teams due to cultural differences in how it is interpreted and evaluated. Study participants processed and interpreted different types of feedback differently, resulting in different preferred types and effects on motivation.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Coaching (Athletics); Coach-athlete relationships; Sports -- Psychological aspects